2003
DOI: 10.1007/s11664-003-0014-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cu content on interfacial reactions between Sn(Cu) alloys and Ni/Ti thin-film metallization

Abstract: The effect of Cu content in Sn(Cu) alloys on the interfacial reaction between Ni thin film and Sn(Cu) alloys has been investigated. We have found that the variation of Cu content has a strong influence on the spalling of the Ni thin film. With small Cu additives in the Sn, spalling was deferred to longer reflowing time. When the Cu content increased to about 1.0 wt.%, a layer of Cu-Sn compound formed on the Ni thin film, and no spalling was observed after 20-min reflowing. The possible mechanism of spalling de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 13 publications
(10 reference statements)
1
25
0
Order By: Relevance
“…For example, a detailed study of the microstructures of the regions next to the Sn/Cu interface revealed numerous tubes and bundles of Cu 6 Sn 5 fibers inside the solder matrix, the formation of which has not been clarified. 13 In a few recent publications [14][15][16][17][18][19][20] the formation of intermetallic layers between Cu-bearing lead-free solders and a Ni substrate or between Ni-bearing lead-free solders and a Cu substrate have been explained by making use of the diagram proposed by Lin et al 21 On the other hand, Hsu et al 22 and Wang and Liu 23 used an earlier preliminary version of the Sn-Cu-Ni isothermal section 24,25 to explain the formation of (Cu,Ni) 6 Sn 5 in soldering reactions between Cu-alloyed Sn-Ag solders and a Ni substrate as well as in the Ni/Sn-3.5Ag/Cu sandwich structure. However, the authors did not consider either the supersaturation of the solder with dissolved Cu and Ni atoms or the existence of the metastable solubility limit.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a detailed study of the microstructures of the regions next to the Sn/Cu interface revealed numerous tubes and bundles of Cu 6 Sn 5 fibers inside the solder matrix, the formation of which has not been clarified. 13 In a few recent publications [14][15][16][17][18][19][20] the formation of intermetallic layers between Cu-bearing lead-free solders and a Ni substrate or between Ni-bearing lead-free solders and a Cu substrate have been explained by making use of the diagram proposed by Lin et al 21 On the other hand, Hsu et al 22 and Wang and Liu 23 used an earlier preliminary version of the Sn-Cu-Ni isothermal section 24,25 to explain the formation of (Cu,Ni) 6 Sn 5 in soldering reactions between Cu-alloyed Sn-Ag solders and a Ni substrate as well as in the Ni/Sn-3.5Ag/Cu sandwich structure. However, the authors did not consider either the supersaturation of the solder with dissolved Cu and Ni atoms or the existence of the metastable solubility limit.…”
Section: Introductionmentioning
confidence: 99%
“…The published results show slightly different values related to the minimum amount of Cu in Sn-based solders which is required to change the primary intermetallic compound from (Ni,-Cu) 3 Sn 4 to (Cu,Ni) 6 Sn 5 between the solder and Ni metallization. [14][15][16][17][18][19][20][21][22][23] For example, Alam et al presented that after 20 min annealing of Sn-3.5Ag-0.5Cu (wt.%) on Ni/Au metallization at 240°C the Cu content of the liquid has decreased to 0.2 wt.%, and that was the reason why (Ni,Cu) 3 Sn 4 started to form between Ni and (Cu,Ni) 6 Sn 5 . 26 Hsu et al annealed the binary liquid SnCu solders on Ni/Ti thin-film metallization at 250°C for different periods of time up to 20 min.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We can clearly observe the appearance of the typical needle-shaped morphology of the (Cu,Ni) 6 Sn 5 compound layer. [7][8][9] After 15 h of current stressing, unlike for the pure Sn/Ni/Cu joint, we found that the interfacial (Cu,Ni) 6 Sn 5 compound layer grew with the current stressing time. After a prolonged 25 h of current stressing, the interfacial (Cu,Ni) 6 Sn 5 compound layer grew even thicker (over 6 lm), much thicker than could possibly form for the same thermal annealing conditions but without the EM effect ( Fig.…”
Section: Resultsmentioning
confidence: 77%
“…[4][5][6][7][8] The Ni underlayer serves as a barrier for Cu diffusion into Sn, causes Cu to dissolve into Ni at a much lower rate than into Sn, allows a certain amount of Sn to diffuse into the Ni layer developing tensile stress in the Sn layer, and delays the growth of Sn whiskers. 9 In addition, the literature states that using a pulsed plating technique can provide Ni deposition with significantly improved properties with respect to those obtained with the traditional direct current (DC) plating procedure. 10,11 Based on the valuable properties of the Ni underlayer, specifically in pulsed plating mode, we have proposed a new composite pulsed plating method as a potential technique to enhance the mitigation of Sn whisker growth.…”
Section: Introductionmentioning
confidence: 99%